Deontological content of the future generation upbringing through national values - Mukhametzhanova, A.O.; Kusainova, M.A.; Imanbetov, A.N.; Ayapbergenova, G.S.; Ramashov, N. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
This article analyzes the peculiarities of the formation of national values formed during the historical development of the material and spiritual culture of Kazakhstan. National values are the basis of spiritual and moral development, personal education, which are preserved in cultural, historical, family traditions and are passed down from generation to generation and ensure the effective development of the country. The author of the article of pedagogical deontology focuses the professional consciousness of the teacher on the fate of the student, on the principles of trust, empathy and justice. In this context, the primary school teacher's main task is to bring the quality of students' education to the international level, educate them in morality, and actively participate in the creation of the educational process on a national basis. In primary school age, the relationship of national culture is of great importance, in promoting the conscious perception of its values, in assimilating national traditions as values, in accordance with which it is necessary to demand norms of behavior. In this context, the primary school teacher argues that being active in building the educational process on a national basis is the greatest burden, the most important thing, the most sacred duty of teaching.
Болашақ ұрпақты ұлттық құндылықтар арқылы тәрбиелеудің деонталогиялық мазмұны
Деонтологическое содержание воспитания будущего поколения через национальные ценности
Keywords: pedagogical deontology; folk pedagogy; folk education; national culture; ethnic values; upbringing; education; traditions